2021
DOI: 10.1007/s11262-021-01872-7
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic sequencing determines complete infectious bronchitis virus (avian Gammacoronavirus) vaccine strain genomes and associated viromes in chicken clinical samples

Abstract: Infectious bronchitis virus (IBV, genus Gammacoronavirus ) causes an economically important and highly contagious disease in chicken. Random primed RNA sequencing was applied to two IBV positive clinical samples and one in ovo-passaged virus. The virome of a cloacal swab pool was dominated by IBV (82% of viral reads) allowing de novo assembly of a GI-13 lineage complete genome with 99.95% nucleotide identity to vaccine strain 793B. In addition, substantial read counts (16% of viral reads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…However, the analysis confirmed the presence of additional eight aa substitutions, but four of them were also found in the Belgian A3B1 reassortant chicken/4439_001/2020 (Accession no. MZ367373 and MZ367374), such as R 133 in VP5, K 359 in VP2, N 787 and V 951 in VP3; and A 667 in VP1 [ 30 ], which showed that there were at least two lineages within this group of reassortants. Unfortunately, only three full genomic sequences of A3B1 strains are available in the GenBank database, making it difficult to determine their diversity at the genetic level.…”
Section: Resultsmentioning
confidence: 99%
“…However, the analysis confirmed the presence of additional eight aa substitutions, but four of them were also found in the Belgian A3B1 reassortant chicken/4439_001/2020 (Accession no. MZ367373 and MZ367374), such as R 133 in VP5, K 359 in VP2, N 787 and V 951 in VP3; and A 667 in VP1 [ 30 ], which showed that there were at least two lineages within this group of reassortants. Unfortunately, only three full genomic sequences of A3B1 strains are available in the GenBank database, making it difficult to determine their diversity at the genetic level.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed the probability of A. fumigatus detection given an SDSSRN of 2, the former standard for A. fumigatus detection. We hypothesised that the probability of mapping a single PMseq read to the A. fumigatus genome is a Bernoulli process, as suggested by Ebinger et al, meaning that the read either mapped correctly or incorrectly (Van Borm et al, 2021). Therefore, we expected the detection probability of A. fumigatus to follow a binomial mass function with increasing SDSSRN.…”
Section: Discussionmentioning
confidence: 95%
“…This method involves random priming and avoids the selection of specific RNA sequences, thus minimizing the biases associated with amplicon-based sequencing and allowing the detection of multiple pathogens [ 22 , 23 ]. However, in clinical samples, the low viral genetic loads and the overwhelming proportion of sequencing reads from the host DNA pose challenges to achieving the complete genome sequences of viruses by metagenomic sequencing [ 29 , 30 , 40 , 41 ]. In this study, the clinical samples, AD04 and AQ10, exhibited relatively low proportions of mapped reads to the reference genome, at 0.85% and 44.63%, respectively, demonstrating the limitation in obtaining the complete genome sequences of IBV directly from clinical samples using SISPA-mNGS.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, these methods have been applied to IBV isolates amplified by serial passage in embryonated chicken eggs [ 26 , 27 , 28 ]. However, despite the need for the mNGS of viruses in clinical tissue samples, variations in amplification due to the low viral genetic load in tissue samples can pose challenges for metagenomic sequencing [ 29 , 30 ]. To circumvent this difficulty, different enrichment techniques employing specific primers targeting the whole genome of the virus have been developed.…”
Section: Introductionmentioning
confidence: 99%